Song 'Happy Birthday" for Bustamante - Miss Lou (Louise Simone Bennett-Coverley), 1919 - 2006; Bennett-Coverley, Louise, (Louise Simone Bennett-Coverley), 1919 - 2006 (Kingston, Jamaica : Jamaica Information Service (J.I.S))
Short clip of Louise Bennett-Coverley singing Happy Birthday tribute to Sir. Alexander Bustamante.
Title adapted from film transcript.
Inaudible due to sound degradation (muffled sound)
Louise Bennett-Coverley
Also available as VHS tape and digital video file.
Videocassette.
Electronic reproduction.
Keywords: Bustamante, Alexander, -- Sir., -- 1884 - 1977; Jamaican politicians; Songs, Jamaican; Jamaica